IP-10 and MIG are sensitive markers of early virological response to HIV-1 integrase inhibitors - Álvarez, Hortensia; Gutiérrez-Valencia, Alicia; Mariño, Ana; Saborido-Alconchel, Abraham; Calderón-Cruz, Beatriz; Pérez-González, Alexandre; Alonso-Domínguez, Jacobo; Martínez-Barros, Inés; Gallego-Rodríguez, María; Moreno, Santiago; Aldamiz, Teresa; Montero-Alonso, Marta; et al. (Frontiers in Immunology, 2023)
Background Interferon-inducible protein-10 (IP-10) and monokine induced by interferon-gamma (MIG) are chemokines recognized as inflammatory biomarkers during HIV-1 infection. We assessed their early and long-term dynamics after initiation of antiretroviral treatment (ART). Methods Persons with HIV-1 (PWH) aged>18 years starting their first ART in 2015-2021 in a prospective cohort (n=73) were included. IP-10 and MIG plasma levels were quantified using a multiplexed bead-based assay. Results IP-10 and MIG plasma levels showed a significant and consistent reduction following ART (80% integrase inhibitor [INSTI]-based) initiation, starting at day 20 and maintained throughout the study period (48 months), paralleling the HIV-1 RNA decay and CD4+ count recovery (p<0·001). At baseline, PWH≥ 50 years, CDC stage C and CD4+ count<350cells/mm3 had higher levels of IP-10 (p=0·022, p=0·001 and p=0·002, respectively) and MIG (p<0·001, p=0·024 and p=0·069, respectively). All of them matched their counterparts several months following ART initiation. MIG levels showed a greater decrease at day 10 in those treated with INSTI (p=0·038). Low-level HIV-1 viremia did not impact MIG or IP-10 levels. Conclusion Plasma IP-10 and MIG showed an early significant decline following ART initiation, with greater early declines in MIG levels in INSTI-based regimens. These findings suggest a strong impact of HIV-1 viremia on IP-10 and MIG levels.